GUIDELINES FOR STATE REGULATION OF THE DEVELOPMENT OF FUNDED PENSION PROVISION IN THE SYSTEM OF SOCIAL INSURANCE POLICY AND POPULATION PROTECTION IN UKRAINE - RUSHCHYSHYN, Nadiya; KRAVCHYK, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study raises the issue of improving the quality of functioning and development of the funded pension system in Ukraine, however, in the context of a much broader and more relevant (especially during the war and its critically acute consequences for human social security - a decrease in income levels and the spread of poverty), high level of external and forced internal migration of the population, loss of work and employment, disability as a result of military operations, increased morbidity, etc.) issues related to social insurance and protection of the Ukrainian population. Arguments are presented in favor of the existence of an objective need for pension reform in Ukraine, in particular through the spread of the principles and provisions of the funded pension system. The shortcomings of the functioning of the domestic social sphere and its system, the system of social insurance and protection of the population, and the functioning of the pension system are pointed out, that do not allow the state to fully ensure social protection of the population in the field of pension provision. The purpose of the study is to outline the prospects for the development of funded pension provision in the system of social insurance policy and protection of the population of Ukraine. A mechanism of state policy and regulation of the development of the social insurance and population protection system in Ukraine has been built, which shows the place and role of funded pension provision. The scientific novelty of the research results lies in outlining the elements of the social insurance and population protection system of the country, as well as in identifying and establishing relationships within it between aspects of pension provision and social security of a person. The applied significance of the research results lies in identifying a number of instruments and means of state policy, the implementation of which will allow improving the quality and increasing the efficiency of the functioning of the domestic pension system.